Analisis Minat Masyarakat Terhadap Perbankan Syariah di Wilayah Kecamatan Panceng Kabupaten Gresik - Nurul Ihsan; Nurrohman Hadi; Muhammad Iqbal Surya Pratikto (Universitas Islam Negeri Fatmawati Sukarno Bengkulu, 2022)
Islamic banking in Indonesia in recent years has experienced extraordinary developments. However, the development of Islamic banking has not been able to attract the Indonesian people to join Islamic banking. As is the case in Panceng sub-district, Gresik district where public interest in Islamic banking is still very lacking. Therefore, the purpose of this study is to find out how the interest of the people in the Panceng sub-district towards Islamic banking. The approach used in this research is a qualitative approach. The results of this study indicate that public interest in the Panceng sub-district is still very low seen from the results of interviews, observations, and so on. This is due to the lack of public knowledge of Islamic banking, then they do not understand the system and operations applied to Islamic banks, as well as a sense of comfort towards conventional banks because they first know conventional banks are also a factor in the lack of public interest in Islamic banking in the region. Panceng District.